PENGARUH NILAI PELANGGAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS NASABAH BANK DAERAH LAMONGAN (BDL) - Luluk Nur Azizah (STIE Mahardhika, 2020)
The concept of service quality, customer satisfaction and service loyalty are related to one another. The relationship between customer value and loyalty is also influenced by product characteristics and purchasing patterns. If the purchase is a routine activity, it is likely that the customer will be loyal to the brand / company. This study analyzes the pattern of relationships between variable values ​​of product attribute performance, level of satisfaction (adequate and desired) and customer loyalty of the Bank Daerah Lamongan. Insidential randomized data was collected from 1364 savings customers and analyzed using the Lisrel 8.30 program. The results of the analysis show that: The value of the aribut performance of savings services received by customers has a significant and positive effect on the level of adequate satisfaction and the level of satisfaction desired. Adequate satisfaction and desired satisfaction levels have a significant and negative effect on customer loyalty in the Bank Daerah Lamongan. This is because the expectations that customers want cannot be fulfilled by attribute performance, resulting in customer dissatisfaction with the attributes. Which exists. Variable level of satisfaction is a mediator and moderator variable for the relationship between Value and loyalty. Also found was a significant and positive direct relationship between value and customer loyalty. As a result of the dissatisfaction with the performance attributes of customers' savings services, customer loyalty is reduced. Factors that have the greatest influence (dominant) on the level of adequate and satisfactory satisfaction are variable staff professionalism in carrying out their duties.